2013
DOI: 10.1002/jbm.a.34548
|View full text |Cite
|
Sign up to set email alerts
|

Bone integration capability of a series of strontium‐containing hydroxyapatite coatings formed by micro‐arc oxidation

Abstract: Strontium-containing hydroxyapatites (Sr-HA) combine the desirable bone regenerative properties of hydroxyapatites (HA) with anabolic and anti-catabolic effects of strontium cations. In the present work, a series of Sr(y)HA [Sr(y)Ca(10-y)(PO4)6(OH)2; y = 0, 0.5, 1, 2] coatings on titanium are produced by micro-arc oxidation (MAO), and the effects of the in vivo osseointegration ability of the coatings are investigated by using a rabbit model. All samples are subjected to biomechanical, surface elemental, micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 50 publications
(125 reference statements)
3
59
0
1
Order By: Relevance
“…concentration may lead to different results of new bone formation and side effects, which meaning that the accumulation of Sr 2? should be paid attention to when applied to human [56,57]. The future study about the biocompatibility of different contents of Sr 2?…”
Section: Discussionmentioning
confidence: 98%
“…concentration may lead to different results of new bone formation and side effects, which meaning that the accumulation of Sr 2? should be paid attention to when applied to human [56,57]. The future study about the biocompatibility of different contents of Sr 2?…”
Section: Discussionmentioning
confidence: 98%
“…10 A recent study has shown that the osteoconductivity of 20% strontium-containing hydroxyapatite (SrHA) used as a coating on implant surfaces results not only in an acceleration but also an improvement in bone-implant integration. 11 There is evidence that strontium (Sr…”
mentioning
confidence: 99%
“…Park et al 35 (2015) e Yan et al 36 (2013) mostraram que os implantes de Ti recobertos com plasma spray de hidroxiapatita apresentavam maiores quantidade de osso na interface osso/implante, quando comparados a implantes com superfície lisa.…”
Section: Discussionunclassified